Effects of branch bending angle on growth and flowering ofwax apple (Syzygium samarangense) - Mohammad Moneruzzaman, Khandaker; Noor Afiza, Badaluddin; Nornasuha, Yusoff (2020)
Wax apple or jambu madu as called by Malay, is a non-climacteric tropical fruit from the family Myrtaceae and scientifically named as Syzygium samarangense. It is native to Malaysia, Indonesia and Philippine. Jambu madu (wax apple) grows to a height of 5–15 m depending on the growing conditions. Manipulating the vegetative and reproductive growthsisthe goal of growers and researchers in agriculture for fruit trees. Bending effects of flowering and fruiting remains the controversial aspect of orchard. However, the optimum bending angle is yet to be elucidated. All the treatments represent different branch bending angle which was at 5° (control), 20°, 45°, 65° and 85°. The results revealed that 65° and 85° provide the best results in terms of enhancing flowering, fruit growth and quality of wax apple fruits. Bending increases the number, as well as the quality of fruit. This study concludes bending has a significant effect on the development and growth patterns of wax apple.